Getfix: Revolutionizing Electronic Equipment Repair through a User-Centric Mobile Application - Dinda Lusita Fristiani Anissa; Ria Andryani (PIKSEL : Penelitian Ilmu Komputer Sistem Embedded and Logic, 2023)
The use of electronic equipment is inseparable from people's lives, in its use electronic equipment often experiences damage but the handling of damaged goods experienced by users is still minimal due to the lack of getting information about relevant and qualified technicians, it is difficult to find a trusted service place and users must bring the items they want to repair directly to the service place, so a system design is needed that can connect users with technicians to be able to repair damaged electronic equipment in the form of mobile applications. In this design, the design thinking method is applied which contains several stages, namely empathize, define, ideate, prototype and test. The application design model is made by considering the target user to facilitate the exchange of information regarding the repair of electronic equipment damage. The results of this study provide a recommendation for the UI / UX design of a mobile application system to call a technician named Getfix, by providing electronic equipment service ordering services and calling technicians online